Computational and experimental studies of salvianolic acid A targets 3C protease to inhibit enterovirus 71 infection - Shi, Sai; Xie, Lei; Ma, Sen; Xu, Binghong; An, Hailong; Ye, Sheng; Wang, Yaxin (Frontiers in Pharmacology, 2023)
Hand foot and mouth disease (HFMD) is a common childhood infectious disease caused by enterovirus (EV) infection. EV71 is one of the major pathogens causing HFMD and is more likely to cause exacerbation and death than other enteroviruses. Although a monovalent vaccine for EV71 has been developed, there are no clinically available anti-EV71 specific drugs. Here, we performed virtual screening and biological experiments based on the traditional Chinese medicine monomer library. We identified a traditional Chinese medicine monomer, Salvianolic acid A (SA), a polyphenolic compound isolated from Salvia miltiorrhiza. SA inhibits EV71 virus infection in a concentration-dependent manner, and its antiviral activity is higher than that of other reported natural polyphenols and has a high biosafety. Furthermore, molecular dynamics simulations showed that SA can anchor to E71, a member of the enzyme catalytic triad, and cause H40 to move away from the catalytic center. Meanwhile, molecular mechanics generalized born surface area (MMGBSA) and steered molecular dynamics (SMD) results showed that the P1 group of SA was most easily unbound to the S1 pocket of 3Cpro, which provided theoretical support to further improve the affinity of SA with 3Cpro. These findings suggest that SA is a novel EV71 3Cpro inhibitor with excellent antiviral activity and is a promising candidate for clinical studies.